P - AND S-VELOCITY IMAGES OF THE LITHOSPHERE-ASTHENOSPHERE SYSTEM IN THE CENTRAL ANDES FROM LOCAL-SOURCE TOMOGRAPHIC INVERSION - Koulakov I.; Sobolev S.V.; Asch G. (My University, 2006)
About 50000 P and S arrival times and 25000 values of t* recorded at seismic arrays operated in the Central Andes between 20°S and 25°S in the time period from 1994 to 1997 have been used for locating more than 1500 deep and crustal earthquakes and creating 3-D P, S velocity and Qp models. The study volume in the reference model is subdivided into three domains: slab, continental crust and mantle wedge. A starting velocity distribution in each domain is set from a priori information: in the crust it is based on the controlled sources seismic studies; in slab and mantle wedge it is defined using relations between P and S velocities, temperature and composition given by mineral physics. Each iteration of tomographic inversion consists of the following steps: (1) absolute location of sources in 3-D velocity model using P and S arrival times; (2) double-difference relocation of the sources and (3) simultaneous determination of P and S velocity anomalies, P and S station corrections and source parameters by inverting one matrix. Velocity parameters are computed in a mesh with the density of nodes proportional to the ray density with double-sided nodes at the domain boundaries. The next iteration is repeated with the updated velocity model and source parameters obtained at the previous step. Different tests aimed at checking the reliability of the obtained velocity models are presented. In addition, we present the results of inversion for Vp and Vp/Vs parameters, which appear to be practically equivalent to Vp and Vs inversion. A separate inversion for Qp has been performed using the ray paths and source locations in the final velocity model. The resulting Vp, Vs and Qp distributions show complicated, essentially 3-D structure in the lithosphere and asthenosphere. P and S velocities appear to be well correlated, suggesting the important role of variations of composition, temperature, water content and degree of partial melting. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CENTRAL ANDES; MANTLE WEDGE; SEISMIC TOMOGRAPHY; SUBDUCTION